Confidence Level in Performing Clinical Procedures Among Medical Officers in Nonspecialist Government Hospitals in Penang, Malaysia. (March 2015) - Othman, Mohamad Sabri; Merican, Hassan; Lee, Yew Fong; Ch'ng, Kean Siang; Thurairatnam, Dharminy
A prospective cross-sectional study was conducted at 3 government hospitals over 6 months to evaluate the confidence level of medical officers (MOs) to perform clinical procedure in nonspecialist government hospitals in Penang. An anonymous self-administered questionnaire in English was designed based on the elective and emergency procedures stated in the houseman training logbook. The questionnaire was distributed to the MOs from Penang State Health Department through the respective hospital directors and returned to Penang State Health Department on completion. The results showed that there was statistically significant difference between those who had undergone 12 months and 24 months as houseman in performing both elective and emergency procedures. MOs who had spent 24 months as housemen expressed higher confidence level than those who had only 12 months of experience. We also found that the confidence level was statistically and significantly influenced by visiting specialist and working together with cooperative experienced paramedics.